IS THE SAHARA ADVANCING SOUTHWARDS? - Michon, P. (BOIS & FORETS DES TROPIQUES, 1973)
African countries bordering on the Sahara are undergoing a prolonged period of dryness which is of iruly caiasirophic proportions, and the question of the extension of the desert arises. Il may be noted that : – Economie development has entailed the deuelopment of industrial crops - peanuts, cation - along with subsistence crops, and this has accelerated deforestation. - The Zapping of branches pracliced by herdsmen to feed their animais ( especially sheep) is oflen a necessity in the Sahelian zone, but in some cases it is practir:erl excessively. - Bush /ires are now more extensive than formerly as is evidencei by the presence of palmyra and calcedrates. What should be done is to generalize early burning outside irrigated areas under cultivation, and to grow unirriguted crops under Acacia alpida, which is a good protection for cultivated soils.